Nas páginas da Revista do Programa de Pós-Graduação em Educação da Universidade Federal de Sergipe (1998-2019) : disputas institucionais, memória histórica e práticas da escrita de um campo - Silva, Wênia Mendonça (2023)
This thesis investigates the trajectory and profile of the institutional journal of the Graduate Program in Education at the Federal University of Sergipe (PPGED/UFS) and, in particular, the production related to the History of Education. The time frame includes the years 1998-2019 and is justified by corresponding, respectively, to the year of the first issue of the magazine and to the year corresponding to the last publication before the change in the editorial profile of the journal, which began to be published in a continuously, and to attend no longer to specific lines of interest, among which the History of Education, but to a comprehensive scope of studies: the Education area. We seek in this academic journal, beyond the writing practices of educational historiography, its phases, in order to understand the struggles fought in this area aiming to achieving legitimacy in terms of scientific production, its organizational forms, the Journal’s idealizing agents and their (re)producers of discourses, so as to also understand the clockwork of the scientific knowledge production in the respective educational field. The theoretical foundation is based on the conceptions of Cultural History, and in the concepts of field and (scientific) capital, by Pierre Bourdieu, and representation, signed by Roger Chartier, in addition to the concept of Generation, founded by Karl Mannheim and Academic Genealogy developed by Cassidy Sugimoto. In this study, the journal under analysis acquires the dual function of object and source. Thus, in addition to the dialogue with the magazine's productions (the documentary collection), we used normative documents as source, such as the opinions and resolutions regarding the functioning of the PPGED/UFS, the transcripts of its meetings and semi-structured interviews with agents of the magazine. The methodological choice was made by the historiographical operation developed by Michel de Certeau, based on the relationship between the products and the places of production, as well as by the content analysis discussed by Laurence Bardin, in order to verify within the narratives how the relative elements to the History of Education materialized in the aforementioned journal. In all, 580 articles were counted among issues, sections and thematic dossiers produced around the areas of interest of the Journal, which, throughout its phases, it was linked to the investigative scope of the PPGED/UFS, its production place. We found that the journal's conjunctural dynamics resulted, over the years, in a contrasting movement between the increase in visibility and the decrease in publications related to the area highlighted in this study, as well as in the limited participation of representative agents in that field. Therefore, we defend the thesis that the journal demonstrated the configuration of the PPGED/UFS academic field, the disputes of the agents in favor of scientific legitimacy and the establishment of groups, acting as space for their identity representation. In addition, the definition of the journal's discursive and thematic priorities were subordinated to the dominant action of the agents in that journal.________________________________________________________________________________________________________________________________